2003
DOI: 10.1177/014556130308200916
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Xanthogranuloma: A Rare Cause of Subglottic Cyst and Stenosis

Abstract: Only two cases ofjuvenile xanthogranuloma ofthe larynx have been pr eviously repo rted in the literature. We report a new case, which occurred in an 18-month-old girl. The patient was brought to us fo r treatment of stridor and respirat ory distress. During examination, she was fo und to have a subglottic mass. The lesion was treated with laser microlaryngoscopy, which relieved the patient's respiratory distress and obviated the need f or tracheotomy. Pathologic examination ofthe mass revealed that it was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The infant in our case report and two other previously published cases 20,21 were managed conservatively without tracheostomy. The patient reported by Naiman et al 21 although doing well initially, had a recurrence of the JXG requiring tracheal reconstruction 6 months after the initial excision.…”
Section: Diagnosis Of Juvenile Xanthogranulomamentioning
confidence: 57%
See 1 more Smart Citation
“…The infant in our case report and two other previously published cases 20,21 were managed conservatively without tracheostomy. The patient reported by Naiman et al 21 although doing well initially, had a recurrence of the JXG requiring tracheal reconstruction 6 months after the initial excision.…”
Section: Diagnosis Of Juvenile Xanthogranulomamentioning
confidence: 57%
“…The patient reported by Naiman et al 21 although doing well initially, had a recurrence of the JXG requiring tracheal reconstruction 6 months after the initial excision. Sahhar et al 20 described another case managed without tracheostomy, however there is no outcome data available. In our treatment decision we considered the risk of tracheostomy in a young infant, as well as the physical and psychosocial burdens tracheostomy carries for the child and the family.…”
Section: Diagnosis Of Juvenile Xanthogranulomamentioning
confidence: 99%
“…To the best of our knowledge, only four cases have previously been reported in English literature [3][4][5][6]. In 1995, Benjamin et al [3] reported the first case of laryngeal JXG which located in bilateral aryepiglottic folds, but the author did not mention any radiological examination.…”
Section: Discussionmentioning
confidence: 97%
“…There was 90-95% occlusion of the subglottic airway. In 2003, Sahhar et al [5] described the subglottic JXG to be a Laryngeal juvenile xanthogranuloma is rare and there were only four cases have been reported previously in English literature. We report a case of isolated JXG of larynx in the superglottic region.…”
Section: Discussionmentioning
confidence: 99%
“…Decanulation was successfully done 11 and 28 months later respectively, after confirmed lesion remission. In the third case, Sahhar [13] confronted a subglotic laryngeal lesion of JXG and treated baby with laser microlaryngoscopy, and reported favorable result without the need for tracheotomy. However Naiman [14] also used similar laser microlaryngoscopy to treat JXG involving the trachea in the fourth case, but after one and a half-year later, flexible fibroscopy showed a relapse, with 50% occlusion of the tracheal airway.…”
Section: Discussionmentioning
confidence: 99%